1999
DOI: 10.1080/j.1600-0412.1999.780905.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of betamethasone on fetal biophysical activities and Doppler velocimetry of umbilical and middle cerebral arteries

Abstract: Betamethasone induces a profound, albeit transient, suppression of fetal breathing, limb and trunk movements, resulting in decreased biophysical profile scores. Awareness of this drug-induced effect might prevent unnecessary iatrogenic delivery of preterm fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…Several studies 5,6,8,13,16 have investigated the effect of betamethasone on Doppler parameters of the MCA and found decreased or unchanged MCA PI levels in different patient groups. In some of these studies, 5,13,16 a PI decrease was observed in both complicated pregnancies and those pregnancies that already had a high MCA PI before betamethasone administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 5,6,8,13,16 have investigated the effect of betamethasone on Doppler parameters of the MCA and found decreased or unchanged MCA PI levels in different patient groups. In some of these studies, 5,13,16 a PI decrease was observed in both complicated pregnancies and those pregnancies that already had a high MCA PI before betamethasone administration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Other studies have evaluated the effects of steroids on the biophysical profile; these studies have revealed reductions in fetal movement, breathing, or amniotic fluid index (AFI), resulting in decreased biophysical profile scores. 8,9 The present study investigated the unanticipated effects of betamethasone on fetomaternal blood flow and AFI.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well documented that fetal breathing movements are reduced by more than 85% [5,10,20] following steroid administration, and fetal body and limb movements by more than 50% [5,10] . Consequently, 45 and 13% of normal fetuses had a biophysical profi le score of 6/8 and 4/8, respectively, 48 h after steroid exposure [11] . Furthermore, the response to vibroacoustic stimulation is similarly suppressed, with 73% of fetuses showing no response or sluggish response 48 h after steroid exposure [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that antenatal corticosteroids suppress central nervous system responses of the fetus, which could lead to the erroneous diagnosis of fetal distress and result in unnecessary iatrogenic delivery of premature infants. Most indicators of fetal well-being, including fetal heart rate (FHR) accelerations and FHR variability [4][5][6][7][8][9] , fetal trunk and breathing movements [4,5,7,10,11] , and response to vibroacoustic stimulation [12] are pharmacologically suppressed by corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Uterinae nachgewiesen werden. Im Gegensatz dazu konnte [9] beim menschlichen Feten keine zirkadiane Rhythmik in Dopplerparametern der A. umbilicalis und A. cerebri media dargestellt werden. In einigen Studien [10,11] zu dieser Thematik bei Neugeborenen wurde eine zirkadiane Rhythmik in der Aorta nachgewiesen [10], nicht jedoch [11] in der A. cerebri media.…”
unclassified